Marot et Du Bellay : « La Renaissance aura lieu si… » - Noirot, Corinne (Renaissance and Reformation / Renaissance et Réforme, 2012)
Some French humanist poets betray a keen awareness of the intrinsic fragility that affects the cultural dynamics of the Renaissance. Marot and Du Bellay express its inchoate nature, even when addressing the King. While celebrating the times they live in, they rarely greet the renewal as an ongoing event. Qualifiers and other linguistic structures make it a virtual reality in their verse. To explain this paradox, this article will first examine the temporal and moral ambivalence affecting humanist poets’ relation to Antiquity. The analysis will then turn to conditional and negative turns of phrase that can be interpreted as oblique warnings to the Prince (“If you do not… then be careful”). Despite the obvious expectation of a budding renaissance, hopes that a French Virgil will emerge are fraught with doubt and virtual wording. Finally, the reluctance toward the epic reveals issues that displace the end of the Renaissance, and perhaps pave the way, if not for a true political renaissance, for a poetics of renaissance as a process.